Determination of change-point of tail index - Gadeikis, Kęstutis (Lietuvos matematikos rinkinys, 2003)
This article deals with a new estimator for tail index, introduced by proof V. Paulauskas in [1]. Hypothesis of a change-point at beforehand-unknown place is examined. Besides simple theoretical calculations, simulation results are presented, which enable to expect successful practical applications of the estimator.